Clinicoradiological and pathological correlations in patients with solitary cysticercus granuloma and epilepsy: focus on presence of the parasite and oedema formation. Issue 3 (September 1995) - Rajshekhar, V; Chacko, G; Haran, R P; Chandy, M J; Chandi, S M
Abstract : A study of the clinical, radiological, and pathological correlations in 43 patients with solitary cysticercus granuloma and epilepsy focused on factors that might help in predicting the presence of the parasite in the granuloma and those that might influence the formation of oedema around the granuloma. The duration of symptoms (< six months and > or = six months) and CT morphology of the granuloma (ring and disc, type A; nodular lesion, type B) were studied as factors that could possibly predict the presence of the parasite in the granuloma. The influence of sex of the patient and the presence of a neutrophilic response in the granuloma on the intensity of oedema around the lesion as seen on CT was also studied. The pathological features were studied in the excised granulomas. The intact or degenerated form of the cysticercus was evident in 22 of 43 specimens. Neither the duration of seizures (P = 0.17) nor the type of lesion on CT (P = 0.16) was predictive of the presence of the parasite in the granuloma. The sex of the patient (P = 0.51) and the neutrophilic response in the specimen (P = 0.73) did not correlate with the degree of oedema on CT indicating that neither of these host factors was a major determinant of oedema production. The findings point to the varied and unpredictable natural history of solitary cysticercus granulomas and the complex nature of host-parasite interactions in individual patients. The inability to predict the presence of the parasite in the granuloma on the basis of the clinical or radiological features precludes a selection of patients with such lesions for cysticidal drug treatment.